Kontradiksi Bumi Papua: Tinjauan Kritis Program CSR PT. Freeport Indonesia di Papua - Fatma Dian Pratiwi (Program Studi Ilmu Komunikasi, 2009)
PT Freeport Indonesia (PTFI) has been operating in Papua since 1967 until finished its join operating agreement in 2041. During those years (until 2005) PTFI claimed that it has been giving so much for the community of Papua with its CSR. But, the fact is there is unfairness between what has taken and given. There is still contradictive between the condition of PTFI on the one side and the Papuan on the other side. They still suffer for hunger, low quality of life and education. This paper tends to portray those unfairness and contradiction.